2020
DOI: 10.1017/s0030605319001145
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the leopardPanthera pardus fuscain Jaipur, India, on domestic animals

Abstract: The ecology and predator–prey dynamics of large felids in the tropics have largely been studied in natural systems where wild ungulates constitute the majority of the prey base. However, in tropical countries where communities are primarily agrarian, the high density of domestic animals in human-dominated landscapes can be a potential prey source for large carnivores. We demonstrate almost complete dependence of the Vulnerable leopard Panthera pardus fusca in the Jhalana Reserve Forest in Jaipur, north-west In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…We found that hyenas are perceived to provide a regulating service to people in the form of promoting urban sanitation in Harar and Mekelle, a cultural service in the form of spiritual support as consumers of jinn in Harar, provisioning services in terms of crop protection in Mekelle and Harar, and of income generation from hyena feeding exhibitions for tourists in Harar. These findings are similar to services provided by urban leopards [ 19 , 29 ]. The abundance of anthropogenic food sources in urban and peri-urban areas—along with human behaviors and policies that accommodate or tolerate hyena presence—have facilitated human tolerance that allows the coexistence of hyenas and humans in some of these cities.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We found that hyenas are perceived to provide a regulating service to people in the form of promoting urban sanitation in Harar and Mekelle, a cultural service in the form of spiritual support as consumers of jinn in Harar, provisioning services in terms of crop protection in Mekelle and Harar, and of income generation from hyena feeding exhibitions for tourists in Harar. These findings are similar to services provided by urban leopards [ 19 , 29 ]. The abundance of anthropogenic food sources in urban and peri-urban areas—along with human behaviors and policies that accommodate or tolerate hyena presence—have facilitated human tolerance that allows the coexistence of hyenas and humans in some of these cities.…”
Section: Discussionsupporting
confidence: 82%
“…City officials and health professionals generally noted instead that the management of free-roaming dogs was the main concern for public health. A similar concern was noted regarding urban leopards in India [ 19 ].…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…In all 3 areas, diet studies indicated that mountain lions expanded their diets in residential areas to include smaller omnivorous or domestic animals (Kertson et al 2011, Moss et al 2016, Smith et al 2016. Similarly, in a reserve outside Jaipur, India, the leopard diet consisted of 90% domestic species, mostly dogs (Kumbhojkar et al 2021). In combination, our landscape use and selection results reflect the behavioral response of mountain lions to development in the Los Angeles area, where being close to humans has costs (e.g., human-caused mortality; Benson et al 2020) and benefits (e.g., higher probability of killing mule deer; Benson et al 2016b).…”
Section: Comparison With Other Studies Of Mountain Lions and Developmentmentioning
confidence: 99%
“…It has been documented that jaguars attack species typically uncommon in their diet (e.g., sea turtles and crocodiles) as a consequence of the decline in the populations of their main prey species (Arroyo-Arce and Salom-Pérez 2015; Pérez-Flores 2018). Predation on domestic animals by large felids is a strategy to survive when density and biomass of wild prey are low (Khorozyan et al 2015), and in humandominated landscapes where the biomass of domestic prey is higher than wild prey (Kumbhojkar et al 2020). Domestic animals such as cattle, sheep or goats are easier to prey upon due to their lack of anti-predatory behavior (Diamond 2002).…”
Section: Introductionmentioning
confidence: 99%